가토 생체내에서 양막을 이용한 자가 결막상피세포 배양 - 우정민; Jung Min Woo; 정우진; Woo Jin Jeung; 박우찬; Woo Chan Park (Daihan angwa haghoi jabji, 2006)
목적 : 양막을 기저막으로 사용하여 생체내에서 자가 결막상피세포를 배양하고 배양된 상피의 특성을 알아보고자 하였다. 대상과 방법 : 6마리(12안) 가토에 구결막에 경첩이 있는 지름 8 mm 원형의 인위적 결막결손을 만든 후 그 위에 약간 작은 직경의 양막을 결막결손 부위에 올린 후 봉합하였다. 1주후 양막 위로 상피가 자라들어 오는 것을 확인하고, 실험안을 적출하여 동결절편을 하였다. 얻어진 조직들은 H&E염색, 결막 술잔세포 뮤신 특이항체(Anti-MUC5AC)를 이용한 면역조직화학염색과 투과전자현미경검사를 시행하여 정상 가토안의 결막구조와 비교하였다. 결과: 12안 중 11안에서 1주 만에 양막 위로 결막 상피화가 이루어졌다. 양막 위에 일주일간 배양된 결막상피에서는 정상 상피세포와 유사한 2～3층의 입방형의 상피세포와 2～3층의 편평상피세포가 관찰되었고 술잔세포를 포함하고 있지 않았다. 결론: 양막을 이용하여 자가 생체내에서 배양된 결막상피세포는 형태학적으로 완전하지는 않았지만, 정상 결막상피와 유사한 미세 소견을 보였다. 양막을 이용한 생체내 자가 결막상피세포 배양법으로 결막상피를 배양하여 결막결손 부위에 이식한다면 기존의 양막을 이용한 방법보다 빠르게 결막 재상피화 시킬 수 있고, 자가 결막이식술에 비해 자가 조직의 결손 및 손상이 없어 결막결손에 효과적이고 안정적으로 사용될 수 있을 것으로 기대된다. <한안지 47(5):812-817, 2006> Purpose: The purpose of this study was to investigate the phenotype of conjunctival epithelial cells auto-cultivated in vivo on human amniotic membrane (CIVAMs) in rabbits for ocular surface reconstruction. Methods: A fornix based-conjunctival flap 8 mm in diameter was made in 12 eyes of rabbits. Amniotic membrane was implanted into the conjunctival defects. Rabbit conjunctival epithelial cells were cultivated in vivo on amniotic membrane for a week. A frozen section was made of the excised specimen. To investigate the phenotype of CIVAMs, Hematoxylin-eosin staining, immunohistochemical staining to anti-MUC5AC (monoclonal antibody to conjunctival goblet cell mucin), and transmission electron microscopy were performed. Results: In 11 of 12 eyes, conjunctival epithelial cells grew successfully on amniotic membrane. Light microscopy demonstrated two to three layers of cuboidal epithelial cells and two to three layers of stratified epithelial cells in CIVAMs. CIVAMs exhibited non-goblet epithelial differentiation as determined by immunohistochemistry to anti-MUC5AC. Transmission electron microscopy of CIVAMs showed fine structure similar to that of normal conjunctival epithelial cells. Conclusions: CIVAMs showed morphological findings similar to normal conjunctival epithelial cells and are expected to accomplish more rapid reconjunctivalization than simple amniotic membrane transplantation. We expect that CIVAMs will be adopted in treating conjunctival burn, symblepharon, conjunctiva-scleral ulcer, and filtering bleb leakage with conjunctival defects. J Korean Ophthalmol Soc 47(5):812-817, 2006 KCI Citation Count: 1